P859 Association of immunopharmacodynamic responses of imprime PGG plus pembrolizumab with clinical benefit in metastatic triple negative breast cancer (TNBC) subjects failing front-line chemotherapy. (15th April 2020) - Ottoson, Nadine; Bose, Nandita; Chan, Anissa; Qiu, Xiaohong; Harrison, Ben; Walsh, Richard; Mattson, Paulette; Gargano, Michele; Cox, Joanna; Chisamore, Michael; Uhlik, Mark; Graff, Jeremy
Abstract : Background: Checkpoint inhibitor (CPI) monotherapies, including pembrolizumab (KEYTRUDA®, pembro), avelumab and atezolizumab have demonstrated modest clinical benefit in chemotherapy-relapsed/refractory TNBC patients (pts) with 5-10% response rate, median overall survival (mOS) of 7-9 months, and 1 year OS 37-40%. TNBC, although more immunogenic relative to the other breast cancer subtypes, is also the most heterogenous, resulting in substantial variability in immune responses. There is a dire need for immunotherapeutic agents that could consistently induce anti-cancer immune responses. Methods: The primary analyses of our Phase 2 study (NCT02981303 ; collaboration with Merck & Co., Inc.) in 44 (intent-to-treat) chemotherapy-refractory/relapsed TNBC pts treated with Imprime PGG (Imprime), a novel yeast derived, Dectin-1 agonist β-glucan PAMP in combination with pembro has shown enhanced disease control rate (25%, N= 11;1 CR, 6 PR and 4 SD>24 weeks), 12-month OS rate (57.3%) and increased mOS (16.6 months) vs the respective endpoints in Keynote086 pts treated with pembro alone. As part of exploratory translational objectives, peripheral blood from pts receiving the combination in 3-week cycles were collected at various time points. Results from serum and cellular immunopharacodynamic (IPD) evaluations from 41 pts are presented. Results: Peak levels of serum circulating immune complexes ( 3 to 22-fold) and complement protein SC5b-9 ( 1.4 to 41-fold) in stage 1 pts provided evidence for Imprime-anti beta glucan antibody immune complex formation. A significant increase in the frequency of HLA-DR+ myeloid cells was observed in the overall population (up to 7.4-fold). In pts showing disease control (N=11), a significant increase in complement function (CH50, 0.8-4 fold range), select chemokines such as MCP-1 production (up to 1000-fold), CD86 expression on monocyte ( 0.5-6-fold) and DC subsets ( 0.8-11-fold), and increased frequency of Ki-67+, HLA-DR/PD-1+ CD8 T cells ( 0.4-14-fold) was observed. Some IPD responses were associated with the 12-month landmark OS analyses. Additionally, enhanced mPFS (HR 0.51; p=0.03) and mOS (HR 0.13; p=0.0013) was observed in 18 pts with >1.25-fold increase in CD86 expression on classical monocytes. Greater than 2-fold increase in the frequency of Ki-67+, HLA-DR/PD-1+ CD8 T cells in 16 pts was also associated with enhanced mPFS (HR 0.395; p=0.01) and mOS (HR 0.183; p=0.008). Additionally, the gene expression profile of these IPD-responders were similar to the RECIST responders with >2-fold upregulation of several genes including IFNg, CD83, GZMA, GZMK, and CD3. Conclusions: Overall, the strong association of the innate/adaptive IPD responses to the clinical responses are suggestive of interplay between the therapeutic mechanisms of Imprime and pembro combination. Ethics Approval: The study was approved by central and local ethics committees depending on site requirements. The central IRB for the study is Western Institutional Review Board (WIRB), approval number 20162506; all sites received IRB approval before opening the study at the respective sites.